Introducing the Community Development Concept in Ukraine: Facilitating Trans-cultural Learning - Timothy Pyrch (Adult Education Research Conference, 2000)
This critical description of efforts to introduce community development processes in Ukraine to prepare the ground for civil society challenges our ability to "walk" our "talk." Development efforts are impeded by controlling behaviours by Canadians and Ukrainians which are more in keeping with centralised control and antithetical to the liberatory tradition in the adult education movement.